The complete mitochondrial genome of a marine mussel, Modiolus comptus (Mollusca: Mytilidae), and its phylogenetic implication - Zhen Zhang; Peizhen Ma; Lisha Hu; Yumeng Liu; Haiyan Wang (Mitochondrial DNA. Part B. Resources, 2019)
In this study, the complete mitochondrial genome of Modiolus comptus was determined and annotated for the first time. The 15,591 bp circular genome has a base composition of 24.3% A, 38.6% T, 12.5% C, and 24.5% G, demonstrating a bias of higher AT content (63.0%) than GC content (27.0%). The mitochondrial genome contains 12 protein-coding genes (PCGs), 20 transfer RNA genes (tRNA), 2 ribosomal RNA genes (12S rRNA and 16S rRNA), and one control region. All genes of M. comptus were encoded on the heavy strand, except trnT(ugu) gene. The whole mitochondrial genome of M. comptus and 21 mitogenomes of other Mytilidae species were used for phylogenetic analysis. The result indicated the newly sequenced species had the closest relationship with Modiolus nipponicus (MK721547) and was clustered within the clade of genus Modiolus.